(untitled) (LACCEI, 2024)
The presence of plastic on beaches has generated that over time it degrades into particles of 5 to 1 mm, known as microplastics, in effect, being of micro size can be ingested by different organisms, causing a highly worrying scenario for life. Therefore, the objective was to determine the significant difference in the presence of microplastics in quantity and weight in supralittoral and littoral zones of six beaches of La Libertad. For this purpose, a quantitative approach was used and the type of research was descriptive, applied, transversal, prospective, observational and non-experimental, the method used was inductive - deductive by means of ANOVA Statgraphics and Minitab, the technique was data collection and the instruments were data collection forms and observation guides. According to the results, with a significance level of 5%, the beach factor effect, the zone effect (littoral and supralittoral) and the interaction of both effects are significant for the factorial model since all the p-values (0.000) are less than 5%.